Building Brands by Helping others Win - Sudarsana Reddy, G.; Muniraju, M. (Indian Journal of Marketing, 2009)
A basic decision in marketing products is branding, in which an organization uses a name, phase, design, symbol, or a combination of these, to identify its products or services of a business and distinguish them from those of competitors. Brand is a means of differentiating a company’s products or services from those of its competitors. A good brand helps company charge premium price for their products or services, since customers prefers to buy good branded product and they will be loyal customers. There is plenty of evidence to prove that customers will pay a substantial price premium for a good brand and remain loyal to that brand. Therefore, it is important for the companies to build brand. At this juncture it better remember MacDonald’s quote that is emphasizing the relationship as an importance factor in building a brand "â€¦it is not factories that make profits, but relationships with customers, and it is company and brand names which secure those relationships". Businesses that invest in and sustain leading brands prosper whereas those that fail are left to fight for the lower profits available in commodity markets. In the globalised business environment every business wants to be a customer’s first choice. Therefore building and managing a brand can play a significant part in making that happen.